Pengaruh Pendapatan Nelayan Terhadap Gaya Hidup dan Polah Konsumsi Masyarakat Rua - Narilah A Tuara; Nurfadila Idris (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to obtain an explanation of the relationship between the Effect of Fishermen's Income on Lifestyle and Consumption Patterns of the Rua Village Community. Based on the results of observations made on February 11, 2022, it was found that the fishermen studied were fishermen of the net/Pajeko group with 21 fishermen members and an executor with non-fixed fishermen's incomes which were obtained by fishermen per day/month. Therefore, this problem greatly affects the lifestyle and consumption patterns of the Rua Fisherman Community. This is evidenced by the SPSS test. From the results of the statistical reliability output, Cronbach's Alpha value is 0.996 with a total of 6 questions. The value of rtable at the 95% confidence level (significant 5%) rtable 0.4227 Thus the Cronbach's Alpha value is 0.768 > 0.4227. The results of the output reliability statistic above obtained a Cronbach Alpha value of 0.999 with a total of 3 questions. The value of rtable at the 95% confidence level (significant 5%) , rtable 0.4227. Thus the Cronbach Alpha value is 0.933 > 0.4227. The results of the output reliability statistic above obtained a Cronbach Alpha value of 0.999 with a total of 3 questions. The value of rtable at the 95% confidence level (significant 5%), rtable 0.4227. Thus the Cronbach Alpha value is 0.926 > 0.4227. From the results of multiple regression, it is known that the Fishermen's Income variable has a significant effect on the Lifestyle and Consumption Patterns of the Rua Community. with a constant value of 4.714 and 12,190 while the value of the regression coefficient for the independent variable/income is 0.214 and -0.256. It is known that the significance value is 0.093 < 0.5 and the calculated F value is 3.116> 3.03. Meanwhile, it is known that the significance value is 0.207 < 0.5 and the calculated F value is 1.700 > 3.03